Direct blood fluorescence signal intensity of neutrophils (NEU-SFL): A predictive marker of death in hospitalized COVID-19 patients? - Fortier, Mathieu; Chea, Mathias; Aïn, Charlène; Loyens, Maxime; Boudemaghe, Thierry; Gris, Jean-Christophe; Bouvier, Sylvie (Frontiers in Medicine, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) is a SARS-CoV-2-induced respiratory disease triggered by immunopathological mechanisms that cause excessive inflammation and leukocyte dysfunction. Neutrophils play a critical role in the innate immunity and are able to produce neutrophil extracellular traps (NETs: NETosis process) to combat infections. Some NETs markers are increased in patients who died from COVID-19. Recently, the neutrophil fluorescence variable (NEU-SFL), available on certain automated complete blood count analyzers, has been correlated with NET formation and may reflect NETosis in patients. Here we evaluate whether NEU-SFL measured after admission of COVID-19 patients is associated with in-hospital survival or death. Patients and methods: 1 852 patients admitted for severe COVID-19 at Nîmes University Hospital in 2021 were retrospectively included in the study: 1 564 who survived the hospital stay and 288 who did not. The NEU-SFL was obtained on the Sysmex™ XN-10® analyzer and values for survivors and non-survivors were compared. The intra-patient NEU-SFL variations between the hospital entry and the last day of hospitalization were also analyzed (IRB 22.06.01, NCT 05413824). Results: Our results showed higher NEU-SFL values in non-survivors. NEU-SFL values above the 4th quartile were independently associated with a 1.60-fold risk of death. Furthermore, the delta NEU-SFL between the first and last days of hospitalization revealed a reverse distribution of patients between survivors and non-survivors. Conclusion: Our pilot study reinforces the role of neutrophils and NETosis in the pathophysiology and prognosis of COVID-19. Further studies combining NEU-SFL with other NETosis markers could improve the management of COVID-19 patients.